2016
DOI: 10.7554/elife.21263
|View full text |Cite
|
Sign up to set email alerts
|

Keeping tabs on fructose

Abstract: Too much fructose in the diet can worsen metabolic problems via a process that involves thioredoxin-interacting protein.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Excessive consumption of these sweeteners has been closely linked to increased risk of NAFLD. 47 Hence, sucrose or HFCS were used singly or combined with high fat in the diet to mimic human dietary style. Although the treatments of dosage, routing, and intervention time varied among these studies, green tea and its components could significantly improve blood biochemical profiles and liver histological parameters and alleviate liver lipids accumulation in different degrees when compared with the control group.…”
Section: ■ Mechanisms and Pathogenesis Of Nafldmentioning
confidence: 99%
See 1 more Smart Citation
“…Excessive consumption of these sweeteners has been closely linked to increased risk of NAFLD. 47 Hence, sucrose or HFCS were used singly or combined with high fat in the diet to mimic human dietary style. Although the treatments of dosage, routing, and intervention time varied among these studies, green tea and its components could significantly improve blood biochemical profiles and liver histological parameters and alleviate liver lipids accumulation in different degrees when compared with the control group.…”
Section: ■ Mechanisms and Pathogenesis Of Nafldmentioning
confidence: 99%
“…Sucrose and HFCS are important ingredients in the modern Western diet. Excessive consumption of these sweeteners has been closely linked to increased risk of NAFLD . Hence, sucrose or HFCS were used singly or combined with high fat in the diet to mimic human dietary style.…”
Section: Potential Preventive Mechanisms Of Green Tea and Its Compone...mentioning
confidence: 99%
“…Recently, some groups reported that there was an indirect pathway mediated by thioredoxin-interacting protein (TXNIP) [ 56 , 57 ]. TXNIP plays an important role in regulating intracellular redox state [ 58 ].…”
Section: Chrebp Regulates Glycolysis and Fructolysis Through Altermentioning
confidence: 99%
“…Even more appealing, many of these engines are free to access. Indeed, game engines have been successfully used to build custom VE experiment tasks (examples include: Deuker et al, 2016;Starrett et al, 2019;Tsitsiklis et al, 2019).…”
Section: Introductionmentioning
confidence: 99%